Accuracy Evaluation of Regional and Global Tidal Models (TPXO9 and Goddard Ocean Tide) at Kabil Tidal Station - Siti Noor Chayati; Muhammad Zainuddin Lubis; Adinda Syahrani (Politeknik Negeri Batam, 2023)
Indonesia is an archipelagic country with a total marine area of 5.9 million km², consisting of 3.2 million km² of territorial waters and 2.7 km² of Exclusive Economic Zone waters, not including the continental shelf. With the vast waters in Indonesia, sufficient information about the tides is needed. Limitations of terrestrial tide data amidst the increasing need for marine information can be overcome by using global and regional tide models. This study uses the regional tidal data model released by BIG (Geospatial Information Agency) and the global tide model TPXO9 and GOT (Goddard Ocean Tides). From the two global tidal models, the tidal harmonic constant values are extracted at the tidal observation point in Kabil. Evaluation of global and regional tide models is carried out by comparing the amplitude values of the main harmonic constants of the tide models of global and regional tides with the amplitude values of the harmonic constants of terrestrial tidal measurement data to obtain a comparison of accuracy. The results of this research show the value of main tidal harmonic.